Teatro de Dança Galpão: experimentações em dança e práticas de resistência durante a ditadura civil-militar no Brasil - Osório, Sofia do Amaral (2015)
In the 1970s, the scenic dance production in São Paulo underwent a major shift. Many artists and groups have departed from the tradition of ballet to try other techniques and invent other ways of thinking and doing dance. In this context, it was created the first space fully dedicated to dance in the city: the Galpão Theatre of Dance. The place was rented by the State Department of Culture and made possible the meeting of people interested in experiments and inventions in dance, serving as a rehearsal and presentation space. In addition, offered free courses from which spectacles were produced, in which choreographers worked together and from what was brought by the students. One of these pieces were Pulsations (1975), choreographed by Celia Gouvêa for the first class of Galpão s students. Through a genealogical analysis mainly based on interviews with people who participated in this event, this research aims to observe the potency of the Galpão experience, from the making of Pulsations, in the context of repression of artistic expressions and practices of freedom of civil-military dictatorship in Brazil